DNA methylation and mRNA expression of SYN III, a candidate gene for schizophrenia - Singh Shiva M; O'Reilly Richard L; Murphy Brenda C (BMC, 2008)
Abstract Background The synapsin III (SYN III) gene on chromosome 22q is a candidate gene for schizophrenia susceptibility due to its chromosome location, neurological function, expression patterns and functional polymorphisms. Methods This research has established the mRNA expression of SYN III in 22 adult human brain regions as well as the methylation specificity in the closest CpG island of this gene. The methylation specificity studied in 31 brain regions (from a single individual) was also assessed in 51 human blood samples (representing 20 people affected with schizophrenia and 31 normal controls) including a pair of monozygotic twin discordant for schizophrenia and 2 non-human primates. Results The results show that the cytosine methylation in this genomic region is 1) restricted to cytosines in CpG dinucleotides 2) similar in brain regions and blood and 3) appears conserved in primate evolution. Two cytosines (cytosine 8 and 20) localized as the CpG dinucleotide are partially methylated in all brain regions studied. The methylation of these sites in schizophrenia and control blood samples was variable. While cytosine 8 was partially methylated in all samples, the distribution of partial to complete methylation at the cytosine 20 was 22:9 in controls as compared to 18:2 in schizophrenia (p = 0.82). Also, there is no difference in methylation between the affected and unaffected member of a monozygotic twin pair. Conclusion The variation in SYN III methylation studied is 1) not related to schizophrenia in the population sample or a monozygotic twin pair discordant for schizophrenia and 2) not related to the mRNA level of SYN IIIa in different human brain regions.